Design and Performance Test of Aluminum Melting Furnace fueled by Used Oil - endramawan, tito; sifa, agus; suwandi, dedi; dionisius, felix (Universitas Muhammadiyah Metro, 2023)
Waste is a major problem in the world and Indonesia. Used oil is one of the liquid wastes produced by machines, both in large industrial and private vehicle engines. Handling this waste oil can be done in various ways, one of which is by using it as a liquid fuel with constant heat treatment. One of the applications of this burning is used in metal smelting equipment to melt metal waste in the community, especially those that have been collected by collectors both in the Indramayu region and Cirebon 3 region. In the design process, a simulation of the safety of the material used is carried out using solid work software using A36 steel. For the performance test, several variations were carried out including the input distance of used fuel oil at a distance of 5 cm, 10 cm and 15 cm and the opening of the used oil tap as fuel in the form of , and 1. The test was carried out using fuel oil to melt 1 kg of aluminium The results of the flow simulation process obtained data with a distance of 10 cm where the airflow is sprayed spread out in the burner and the optimal parameter at the time of smelting is that with a tap opening it will be more effective in fuel use and aluminium smelting time.